Prophylactic antibiotics prior to dental procedures: A cross-disciplinary survey of dentists and medical providers - McCarthy, Morgan; Andrews, Rebecca; Banach, David B. (American journal of infection control, 2020)
•A survey of medical providers and dentists revealed that prescribing prophylactic antibiotic prior to dental procedures was common.•There were significant differences in beliefs and influences in prophylactic prescribing between groups.•Both groups expressed interest in additional education on prophylactic antibiotic prescribing prior to dental procedures. The prescription of prophylactic antibiotics prior to dental procedures is common, although factors influencing prescribing are poorly understood. We surveyed general and specialist medical providers and dentists on beliefs and attitudes regarding prophylactic antibiotic prescribing prior to dental procedures. There were significant differences in factors influencing decisions and perceived responsibility regarding prophylactic antibiotic prescribing between groups, although interest in additional education on the subject was high across both groups.